The operative assistance dynamics of the Venezuelan military nurse - Claudia Ermely Izquierdo Martínez; Celia Ledo Royo; Jorge Montoya Rivera (Centro Provincial de Información de Ciencias Médicas, 2017)
This investigation is intended to diminish the inadequacies in the process of the military nurse training, so that their professional performance could be improved.  The operative assistance dynamics of this specialist is approached with that purpose.  It contains configurations and dimensions that particularize it in their professional training; new relationships and categories are also declared for the development of their operative practice, with the logic that should be followed in this theoretical construction: from the general fields to the singular ones and vice versa.